(3GdJYQja HehdGfGYHOGdSdGe hHYV efGbHgs - (3GdaGWej GdTQGOjs; (3CHh GdQHjY SdjeGf Hf eMeO Hf YHO Gddg GdTaTGhfj GdaGSj, GdMhGJ,J (B1231 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdTjN ehdGfG YHOGdSdGe gh bWH GdCbWGH , hef Ydjg GdeOGQ aj adc GdCSHGH Edi WQjb eYQaI QH GdCQHGH s
(3BNQgG (B:s
(3hbjd (B: (3CQHYI hYTQjf , hbjd SJI hYTQjf hSJeGFI CfXQ HSW Pdc ai JQLeI CHj YHOGddg eMeO Hf GdWGgQ Hf YHOGdhgGH QV Gddg Yfg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B183 - (3U(B206s
(3hgh oeNJUQ GdQhVI GdebUhOI ai HTGFQ Hfj ShOI dCHj GdQHjY SdjeGf Hf eMeO GHf YHOGddg Hf eMeO GdTaTGhfj GdTgjQ HGdMhGJ hGdeJhaj SfI (B1231(3g`s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B133s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B115 s
Keywords: (3GdJGQjNs